INTERELASI EKONOMI DAN COVID-19 (Tela’ah Tantangan Ekonomi dan Bisnis Syari’ah) - Muslih Aris (Ekosiana Jurnal Ekonomi Syari ah, 2021)
The Covid-19 pandemic is currently sweeping the world including Indonesia, which has had various impacts including the economic sector.This study aims to determine the impact of the Covid-19 Economic and Sharia Business challenges in Indonesia. This type of research is a type of library research and using the qualitatif analysis. The results of this study indicate the impact of the Covid-19 Pandemi that occurred on the global economy including the economy in Indonesia. From this pademic impact the decline in demand for sharia products and hampered production of sharia because raw materials come from outside countries, the impact of this pademic affects this hampered the realization of investment. No exception, investors who plan to invest their capital in Islamic businesses. Increasing the risk of Islamic financial institutions from this challenge Sharia economic and business strategies can overcome the impact of the Covid-19 pademic. It is expected that Islamic economic and business actors show empathy and solidarity with stakeholders. Sharia business people compile more profitable business strategies. Sharia business actors utilize and support stimulus programs from the government. Islamic banking and other financial institutions must start revising growth targets, applying digital transaction technology in one solution. Sharia economics and business can play a role in restoring economic shocks by prioritizing the attainment of sharia objectives (sharia maqashid) Keywords: Covid-19 Impact, Indonesian Economy, Sharia Economy and business. Keywords : The Impact Of Covid-19, Challenge, Economy and Syariah Business DAFTAR PUSTAKA Alexander B, Hilda. “Tiga Skenario Dampak Covid-19, ‘New Normal’ Hingga ‘Survival.’ Kompas.Com Last modified 2020. https://properti.kompas.com/read/2020/04/13/144734421/tiga-skenario-dampak- covid-19-new-normal-hingga-survival?page=all#page2. Badan Pusat Statistik. “Tingkat Pengangguran Terbuka.” Badan Pusat Statistik Indonesia. Last modified 2020. bps.go.id. Muniarti, dkk. “Tujuh Paket Ekonomi Dan Keuangan Syariah Dalam Mengatasi Dampak Covid 19.” Mysharing.Co,Id. Last modified 2020. http://mysharing.co/tujuh-paket- ekonomi-dan-keuangan-syariah-mengatasi-dampak-krisis-Covid-19-19/. Handayani, Diah, Dwi Rendra Hadi, Fathiyah Isbaniah, Erlina Burhan, and Heidy Agustin. “Penyakit Virus Corona 2019.” Jurnal Respirologi Indonesia 40, no. 02 (2020) Iskandar, Azwar, Bayu Taufik Possumah, and Khaerul Aqbar. “Peran Ekonomi Dan Keuangan Sosial Islam Saat Pandemi Covid-19.” Salam: Jurnal Sosial dan Budaya Syar’i 07, no. 07 (2020) Juli Efrianto, Eeng. “Prosedur Dan Biaya Audit (Studi Komparatif Konvensional Dan Syariah).” AL Intaj 05, no. 01 (2019) Laras Widyaningrum, Gita. “WHO Tetapkan COVID-19 Sebagai Pandemi Global, Apa Maksudnya?” Nationalgeographic.Co.Id. Last modified 2020. https://nationalgeographic.grid.id/read/132059249/who-tetapkan-covid-19-sebagai- pandemi-global-apa-maksudnya. Masyarakat ekonomi Syariah. “Nasib Keuangan Syariah Di Tengah Pandemi Covid-19.” MES Indonesia. Last modified 2020. Nugraha, Daniel. “Dorong Pertumbuhan Ekonomi, Ini 3 Stimulus Pemerintah Untuk Atasi Dampak Corona.” Paper Blog. Last modified 2020 . https://www.paper.id/blog/bisnis/stimulus-pertumbuhan-ekonomi-untuk-corona/. Nursanti, Ari. “Media Tiongkok Sebut WHO Nyatakan Seluruh Bukti Tunjukkan COVID-19 Berasal Dari Kelelawar.”Pikiran rakyat.Com. Last modified2020. https://www.pikiran-rakyat.com/internasional/pr-01370279/media-tiongkok-sebut-who-nyatakan-seluruh-bukti-tunjukkan-covid-19-berasal-dari-kelelawar.Sari, Milya, and Asmendri. “Penelitian Kepustakaan (Library Research) Dalam Penelitian Pendidikan IPA.” NATURAL SCIENCE: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 06, no. 01 (2020) Sulaiman, Fajar. “Hai, Pelaku UKM! Ini 5 Strategi Hadapi Dampak Covid-19.” Warta Ekonomi. Co.Id. Last modified 2020. https://www.wartaekonomi.co.id/read277929/hai-pelaku-ukm-ini-5-strategi-hadapi- dampak-Covid-19-19. Supriatna, Eman. “Wabah Corona Virus Disease Covid 19 Dalam Pandangan Islam.” SALAM; Jurnal Sosial & Budaya Syar-i 07, no. 06 (2020) Susilo, Adityo, C Martin Rumende, Ceva W Pitoyo, Widayat Djoko Santoso, Mira Yulianti, and Robert Sinto. “Coronavirus Disease 2019: Tinjauan Literatur Terkini Coronavirus Disease 2019: Review of Current Literatures.” Jurnal Penyakit Dalam Indonesia 07, no. 01 (2020) Syakir, Ahmad. “Pemberdayaan Ekonomi Umat Islam Indonesia Melalui Wakaf Produktif.” AL Intaj 02, no. 01 (2016)